Teaching Adolescent Struggling Readers in the European Union. A Comparative Study of Good Practices in European Countries (ADORE-project) (Training and Practice : Journal of Educational Sciences, 2010)
In 2006 the European Commission of Education defined as a priority to develop an international network of adolescent literacy researchers and practitioners, in order to understand the special needs of adolescent struggling readers, and to provide a guide on good practices in a theoretical framework. The invitation to a EU tender (SOCRATES Programme: General activities of observation, analysis and innovation", Action 6.1.2. and 6.2.) initiated a multidisciplinary dialogue between reading researchers to produce case studies and suggestions in reading instruction for EU policy makers. The main aim is to point out effective methods concerning struggling readers' needs. The other main objective is to develop a handbook about good practices for reading researchers, teachers and other professionals being involved in the field of adolescent literacy